Biosorption of lead by postassium permanganate modified and unmodified calamansi (Citrus microcarpa) peel - Palmes, Rio Bronzal (University of the Philippines Visayas, 2016)
For heavy metals removal from polluted water, the vapplication of biosorption has been a significant research area inthe past decades with much attention given on the absorbent materials to be used. In this study, the potential of potassium permanganate (KMnO4)-modified calamansi (Citrus microcarpa) peel as biosorbent for lead was tested.